2023
DOI: 10.1017/s135561772300036x
|View full text |Cite
|
Sign up to set email alerts
|

Time-lagged associations between two adverse childhood experiences and later-life cognitive function through educational attainment and stroke

Abstract: Objective: Adverse childhood experiences (ACEs) have been associated with worse cognitive health in older adulthood. This study aimed to extend findings on the specificity, persistence, and pathways of associations between two ACEs and cognition by using a comprehensive neuropsychological battery and a time-lagged mediation design. Method: Participants were 3304 older adults in the Health and Retirement Study Harmonized Cognitive Assessment Protocol. Participants retrospectively reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Moreover, recent research has identified specific adverse experiences that may further exacerbate cognitive declines by influencing educational attainment. For instance, one study demonstrated a robust and enduring indirect association between parental substance abuse and poorer cognitive function in later life, mediated through educational level ( 16 ). Similarly, Halpin et al observed that heightened childhood adversity could amplify susceptibility to cognitive impairment by shaping the early educational experiences of older adults ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent research has identified specific adverse experiences that may further exacerbate cognitive declines by influencing educational attainment. For instance, one study demonstrated a robust and enduring indirect association between parental substance abuse and poorer cognitive function in later life, mediated through educational level ( 16 ). Similarly, Halpin et al observed that heightened childhood adversity could amplify susceptibility to cognitive impairment by shaping the early educational experiences of older adults ( 17 ).…”
Section: Introductionmentioning
confidence: 99%